The Effect Of Environmental Performance On Firm Value Using Financial Performance As Mediator Variable - Nurul Aini; Nabilah Taqiyyah Faisal (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This study aims to examine the effect of environmental performance on firm value directly or indirectly by employing financial performance as a mediator variable. Design/methodology/approach: This research employs quantitative research. The population of the research is all non-financial companies on the Indonesia Stock Exchange (IDX) in the 2014-2019 period with a sample of 282 firm-years. The employed data analysis technique is Warp PLS 6.0 carried out in the two testing stages; the testing of the direct and the indirect effects of environmental performance variable on firm value. Findings: Environmental performance has a significant positive effect on firm value; environmental performance has no effect on financial performance; financial performance has a significant positive effect on firm value; and financial performance is not proven as a variable that mediates the effect of environmental performance on firm value. Research limitations: The measurement of financial performance employs only one proxy; ROE. Measurement of financial performance may use various proxies to produce more accurate findings. Practical implications: This research provides an overview of the importance of implementing environmental performance for a company in order to increase firm value or company reputation among investors in particular and society in general. Originality/value: This research is a development of previous studies, which produced varying research results, with the addition of financial performance as a mediator variable. Paper type: This research is categorized as a research paper. Keywords: Environmental Performance, Financial Performance and Firm Value